The Effect of Implementing Clinical Nursing Practice Guideline for Dietary Control on Dietary Control Behavior and Blood Sugar Level in Muslim Patients - แวและ, ฮามีด๊ะ; ชิณวงศ์, ทิพมาส (Princess of Naradhiwas University Journal, 2018)
This quasi-experimental research, two groups pre-post test design, were to evaluate the effect of implementing clinical nursing practice guideline for dietary control on dietary control behavior and blood sugar level in Muslim patients with uncontrolled diabetes, who attended at Naradhiwasrajanagarindra hospital was performed. The subjects were divided into two groups. The control group (n = 30) were received usual nursing care, and the experimental group (n = 30) were received clinical nursing practice guideline for dietary control, were 1) The clinical nursing practice guideline for dietary control 2) The booklet to promote dietary control for Muslim patients with uncontrolled blood sugar, and 3) The education plan to promote dietary control. The duration of this study was 8 weeks. Data collecting tools were 1) The Demographic and Health Data Collecting Form, 2) The Dietary Control Behavior Questionnaire, testing reliability used Cronbach’s alpha coefficient and gained the result of 0.80 and 3) Blood Sugar Measurement Tool. Analyzed by descriptive statistics, Chi-square and t-test. The study results were as follows: 1) Mean score of the dietary control behavior in the experimental group after receiving the clinical nursing practice guideline for dietary control was statistically significantly higher than before (p < .001) and higher than those in the control group (p < .001) 2) Mean score of the blood sugar level in the experimental group after receiving the clinical nursing practice guideline for dietary control was statistically significantly lower than before (p < .001) and higher than those in the control group (p < .001). This study there are suggestions. Clinical nursing practice guidelines should be used to promote the use of dietary control in Muslim patients with uncontrolled diabetes with adaptation and development.